If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + 3s = 4 Solving 1 + 3s = 4 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 3s = 4 + -1 Combine like terms: 1 + -1 = 0 0 + 3s = 4 + -1 3s = 4 + -1 Combine like terms: 4 + -1 = 3 3s = 3 Divide each side by '3'. s = 1 Simplifying s = 1
| a+1+a+3+2a=90 | | x*y=31 | | 16f=1.8+32 | | c=2a+3 | | m/36=2 | | dxy=31 | | F(x)=-2x^2-5x+7 | | 7(x+5)+5=9x-2(x-4) | | 70=6p+34 | | 16=2a+5 | | 3x+5+6x-9=-4 | | -45=32 | | 4=-7s+53 | | 6b-3b=0 | | 50+d=2d | | 5x+x+20+40=180 | | x+y-12x+8y-8=0 | | 5x-64/9=64 | | 7(4y+5)=19+8 | | -u+2=220 | | w=x(y/z) | | N/0.6=8 | | 6=3a+3 | | 30-x=5x+6 | | -43+x=23-2x | | 33.6=H^(3/2) | | 2w+10=48 | | 6x+2(5x-5)=8-3(2x+1) | | 60=256-x | | 5.9h+2.15=20 | | 3x+23+7x-37=180 | | 1-4cosx=-3 |